Cross-Cultural Management in Global Workplaces : Its Impact on Expatriate Job Satisfaction, Integration, and Performance - Rodriguez Quiroga, Mariana; Petrů, Jaroslav; Schmitt, Judith; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2025)
This research examines the impact of cross-cultural management (CCM) on the job satisfaction, integration, and performance of expatriate employees working in Europe, and uses as foundation three theoretical models: Cultural Intelligence Theory, Hofstede’s Cultural Dimensions, and Herzberg’s Two-Factor Theory. These combined perspectives helped capture both general patterns and personal experiences related to cultural adjustment and workplace dynamics. To get a complete understanding of the findings, the study followed a mixed-methods design: For instance, quantitative data was collected through surveys, employing validated instruments like the MSQ and the CQS, while the qualitative findings came from semi-structured interviews with fifteen expatriates currently working in various European countries. The study findings conclude that there is a strong relationship between cross-cultural management and both job satisfaction and integration among expatriates. Similarly, cultural intelligence also contributed positively, though in a more complementary role. Interestingly, performance did not show a statistically significant relationship with cross-cultural management, which allowed to suggest that this variable may be influenced by other external or role-specific factors. Based on the attained results, the research provides practical suggestions for organizations that are looking to develop leaders who are culturally aware and sensitive to differences, individualized motivation plans, and inclusive integration programs. By doing so, it hopes to contribute to a more human-centered and globally conscious approach to leadership, one where diversity is not only acknowledged, but truly empowered.
Vedoucí práce: Jaroslav Petrů
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: management [obor dipl. práce]; diplomové práce; master's theses